Psychological correlates of eating behavior in overweight/obese adolescents in Taiwan: Psychometric and correlation analysis of the Three-Factor Eating Questionnaire (TFEQ)-R21 - Yu-Wen Lin; Chung-Ying Lin; Carol Strong; Chih-Hsiang Liu; Yi-Ping Hsieh; Yi-Ching Lin; Meng-Che Tsai (Pediatrics and Neonatology)
Background: The Three-Factor Eating Questionnaire (TFEQ) is a self-assessment scale used widely in the studies of eating behavior, but its short form TFEQ-R21 has not been validated in the Taiwanese population. This study aimed to assess the factor structure and reliability of TFEQ-R21 and to identify the correlates of eating behavior in obese and non-obese Taiwanese adolescents. Methods: A total of 445 individuals aged 13–15 years were analyzed. They self-reported their eating disorder behavior, body shape preoccupation, weight-related self-stigma, anxiety, and depression. We applied a confirmatory factor analysis to test the model fit of TFEQ-R21 for the three pre-conceptualized domains in the data. Further univariate and multivariate linear regression analyses were applied to identify the correlates of different TFEQ-R21 subdomains. Results: The Comparative Fit Index for the TFEQ-R21 was 0.908, which confirmed the three-factor structure (i.e., cognitive restraint [CR], uncontrolled eating [UE], and emotional eating [EE]) in the Taiwan version of TFEQ-R21. Only CR correlated with disordered eating (r = 0.351, p < 0.001). Body shape discrepancy, rather than weight status, was associated with CR in both males (β = 0.15, 95% odds ratio [CI] 0.05–0.25) and females (β = 0.21, 95% CI 0.10–0.32). Gender differences were noted in the correlates of UE and EE, where ideal body shape in males and self-perceived stigma in females were the main associative factors. Conclusion: The Taiwan version of the TFEQ-R21 is a robust, reliable tool by which to measure adolescent eating behavior. Gender differences in the eating behavior correlates require clinical and public health attention when implementing weight management programs.